2014
DOI: 10.1111/jam.12578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drinking water conditions and copper materials on downstream biofilm microbial communities and Legionella pneumophila colonization

Abstract: Aims: This study examined the impact of pipe materials and introduced Legionella pneumophila on downstream Leg. pneumophila colonization and microbial community structures under conditions of low flow and low chlorine residual. Methods and Results: CDC biofilm TM reactors containing either unplasticized polyvinylchloride (uPVC) or copper (Cu) coupons were used to develop mature biofilms on Norprene TM tubing effluent lines to simulate possible in-premise biofilm conditions. The microbial communities were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 57 publications
3
57
1
Order By: Relevance
“…; Lu et al . ). Slower biofilm formation on copper compared to polyethylene may be due to its antibacterial properties (Lehtola et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…; Lu et al . ). Slower biofilm formation on copper compared to polyethylene may be due to its antibacterial properties (Lehtola et al .…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have shown separated clusters between different materials in stagnated waters or biofilms (Lu et al . ; Ji et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations